The sources Of Military Change : Culture,Politics,Technology - Edited by Farrell, Theo and Terriff, Terry (Rawalpindi Army Publishing House, 2002)
In varying circumstances, military organizations around the world are undergoing major restructuring. This book explores why, and how, militaries change.
Keywords: The sources Of Military Change : Culture,Politics,Technology -- Militry -- Military art and science -- Civil-military relations